Development of learners' intercultural communicative competence through English language textbooks: A directed qualitative content analysis - W. Indumini Darshika (The Open University of Sri Lanka, 2024)
In the contemporary world, intercultural competence is vital to fostering understanding among people from diverse backgrounds. Therefore, the acquisition of intercultural awareness has become a fundamental component in all language learning programmes. Through directed qualitative content analysis, this study investigates to what extent the content of the Grade 11 English Language textbook in the Sri Lankan government school context contributes to develop 'intercultural communicative competence' (ICC) in learners. The contents were analyzed against Byram's (1997) Intercultural Communicative Competence Model, types and categories of culture, and representation of ethnicities in the selected textbook. The findings revealed that the textbook represents different ethnicities through its characters (e.g. Vikum, Chamindu, Farah, Kamalesh, Nithya, Rikaz, etc.) although it does not reflect the actual religious/ethnic makeup of Sri Lanka. Moreover, the textbook most often refers to the big "C" (visible culture) while less attention is paid to the small "c" (invisible culture). Additionally, the contents predominantly represented universal cultural aspects and the source culture while briefly referring to target and international cultures. In addition, the cultural content was presented as factual knowledge with fewer opportunities for critical analysis and reflection. Consequently, students do not get the opportunity to reflect on stereotyping and counter pre-formed biases. Hence, it would be better to go beyond portraying the religious/ethnic groups through characters to enable a more analytical approach to learning about other cultures. Based on the findings, the learning material developing authority should make certain amendments to the ESL textbooks to increase their content value and quality. In conclusion, culture teaching should be integral in language programmes and material developers should represent different ethnicities.